1919. Outpatient Care-Seeking Prior to Acute Respiratory Infection Hospitalization in the United States, 2012–2014. (26th November 2018) - Fowlkes, Ashley; Chen, Jufu; Reed, Carrie
Abstract: Background: Acute respiratory infection (ARI) diagnoses encompass syndromes such as pneumonia and bronchiolitis, and are among the leading causes of hospitalization. While outpatient care could present an opportunity to prevent subsequent hospitalization, few studies have measured healthcare utilization preceding hospitalization. We characterized outpatient visits in the 2 weeks prior to ARI hospitalization using commercial insurance and Medicare claims in MarketScan from 2012 to 2014. Methods: We included inpatients with an ICD9 discharge diagnosis for ARI (460–466), pneumonia (480–486), or influenza (487–488) and evaluated outpatient records ≤14 days prior to admission, excluding the day of admission. We defined an outpatient visit as health encounters with a reasonable potential for medical care receipt (e.g., medical device delivery). We used the previous 12 months of medical records to define patients' Charlson Index and health care utilization, including any prior hospitalizations and preventive and ambulatory care sensitive condition (ACSC) visits. Severe outcomes were defined as intensive care unit admission or death. We used multivariable logistic regression stratified by age group to evaluate demographic, clinical, health utilization, and outcome factors associated with outpatient care prior to admission. Results: We identified 407, 096 ARI hospitalizations, among which 60% of patients had ≥1 outpatient visit prior to admission; 36% of visits occurred 1 day prior to admission. Children aged <1 were more likely to have a preceding visit compared with other age groups (67% vs. 57% to 59%, P < 0.001). In all age groups, persons with preventive care and ACSC visits in the past year, a Charlson score ≥1, female sex, noncapitated health plans, and salaried employment were more likely to have a preceding outpatient visit. Patients with severe outcomes were significantly less likely to have a preceding visit, while specific diagnoses varied by age group (figure). Conclusion: In a population of insured individuals, only 60% received outpatient care in the 2 weeks prior to ARI hospital admission. A greater understanding of healthcare seeking behaviors for potentially preventable hospitalizations is needed. Disclosures: All authors: No reported disclosures.